Ring, Claude; Ring, Mary. Floor plan of the Ring shed. - LaDuke, John (2013)
Contemporary floor plan of the shed next to the Ring house built by Claude Ring. Measurements and floor plan completed by LaDuke for the Quidi Vidi Field School 2013.